Application of visual didactic regulators in distance learning - V. E. Steinberg; R. M. Asadullin; D. R. Fatkhulova; I. R. Tagariyeva (Russian State Vocational Pedagogical University, 2022)
Introduction. In the process of developing distance learning and changing the forms of educational materials used in different countries, there are such problems as the lack of direct communication, insufficient control of the educational process and low motivation. The effectiveness of the guiding and orienting influences of the teacher, his/her professional and creative teaching methods is decreasing. As a result, the implementation of cognitive learning activities by students becomes more difficult, and the dependence of its results on self-organisation and self-control increases. These problems are inherent in distance learning in many countries, including the Russian Federation, where a network of federal innovation platforms is being created to improve distance learning and to promote educational innovations. The hypothesis assumes the expediency of research and applied development of universal methods and means to reduce negative phenomena in distance learning.Aim. The present research aims to study the methods and means of additional presentation of the plan of educational activity and the results of its implementation in the form of visual didactic regulators; to create software and methodological tools for the introduction of regulators in distance learning; to experimentally test applied developments.Methodology and research methods. The study is based on the didactic principle of visibility, which is necessary to provide the student with information about the plan of the educational activity being performed and to present the results of its implementation in the form of visual regulators. Logical-semantic modelling of knowledge was used to design regulators; an integrated approach was applied in the development of software and methodological tools for the application of regulators. In the course of experimental testing (teachers of rural schools, teachers and students of the university), questionnaires, surveys and observations were carried out.Results and scientific novelty. An analysis of the work of teachers demonstrated the relevance of using visual aids with illustrative and reference properties in the context of distance learning. It is proposed to supplement the educational task in text form with a plan using a visual didactic regulator, and the results of the implementation of the plan in the accepted form should also be supplemented by a didactic regulator. The use of regulators contributes to the self-organisation and self-control of the student, the development of universal educational actions in the construction of regulators and in educational activities, the improvement of systematic thinking and the formation of models for the implementation of educational activities. Software and methodological tools are proposed to support the introduction of didactic regulators into distance learning.Practical significance. The developed didactic solutions and software methodology tools complement the means and methods of distance learning technology, make it possible to increase the effectiveness of communication between the teacher and the student, as well as the guiding, orienting influences of the teacher; allow to increase the dependence of learning out-comes on self-organisation and self-control of the student.